Immunization E-Book Application Using Web-Based Object Oriented Method - Muhammad Rizki; Boni Oktaviana Sembiring; Eka Rahayu (CESS (Journal of Computer Engineering, System and Science), 2023)
The digital era, where all activities can be done using technology. Including about books that can turn printed books into digital books or E-books. Immunization is the process of making a person immune or immune to a disease. The type and schedule of immunizations will determine the health of their toddlers both now and in the future. Parents' ignorance of the type and stage of the immunization schedule is an obstacle for parents. To find out the types and stages of the immunization schedule, parents should read a guide book containing information on immunizations. With immunization books that are still conventional, books become less effective due to carelessness, such as being easily damaged and lost. To prevent and reduce these problems the author wants to design an E-book application or a web-based digital version of a book that can be used as a source of immunization information. In designing this application, the author uses the Object Oriented method, namely Object Oriented Analysis and Design (OOAD) for the system development method and Oriented Programming (OOP) for making the application. With the Immunization E-book Application using the Web-based Object Oriented Method, it is hoped that the general public, especially parents with toddlers, doctors and nurses can find out information about Immunization data quickly anytime and anywhere.